Letter to editor Feedback on cases of dengue fever reported at Nawabshah. - Shamsuddin Shaikh. , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
The dengue outbreak in the country appears to be crossing the previous record of 2011 when 27,000 people were affected by the mosquito- borne disease.However, this time deaths caused by dengue are expected to be minimal as compared to 2011 when 370 people lost their lives due to the painful disease.During the current year, 42 deaths have been caused by dengue so far and health practitioners attribute the lower mortality rate due to better availability of surveillance and curative measures.